Assessing the Brand Equity of Majid Brand in Comparison with Nike from the Perspective of Iranian Consumers - Morteza Rezaei; Esmaeil Sharifian (Shahid Bahonar University of Kerman, 2021)
The importance of brand equity is due to its strategic role in gaining a competitive advantage in the market. The purpose of this study was to assess the brand equity of Majid in comparison with Nike from the perspective of Iranian consumers. The research method was survey in terms of data collection and descriptive-correlation in terms of research method. The statistical population of this study was sport good consumers in the range of 18 to 45 years old. 384 sport good consumers completed an online questionnaire through random sampling. The reliability of the questionnaire was calculated based on Cronbach's alpha coefficient. Results of the Pearson correlation test revealed that there is a significant relationship between brand equity and its components in both brands. The results of the paired t-test, revealed that the Nike brand has higher brand equity than Majid brand according to the perspectives of Iranian consumers. Also, for the Iranian consumers, the quality of the brand is the most important element of brand equity.